Hubungan Umur dan Konsumsi Makanan Mengandung Zat Besi dengan Anemia pada Ibu Hamil di Puskesmas Talise Palu - Susan Elviyaningsih; Rafika; Putu Candriasih (Poltekkes Kemenkes Palu, 2018)
Anemia in pregnant women is called a potential that endangers the mother and child, therefore anemia requires serious attention from parties involved in health services. The purpose of this study is to know the relationship of age and consumption of iron-containing foods with the incidence of anemia in pregnant women in Talise Palu Health Center in 2017. The type of research is descriptive comparative using a cross sectional approach. The population of all pregnant women in the Talise Health Center area. The sample in this study amounted to 55 respondents with the sampling technique using consecutive sampling technique. The data collection is done through direct interviews and direct Hb measurements. Data analysis using univariate frequency distribution and bivariate analysis with Fisher's Exact Test. The results of the study of 55 respondents there were 96.4% of pregnant women who had anemia, with the age of pregnant women not at risk of 85.5% and pregnant women who rarely consumed foods containing iron there were 78.2%. The results of statistical tests using Fisher's Exact Test showed that there was a relationship between consumption of iron-containing foods (p = 0.04) with the incidence of anemia in pregnant women at Talise Palu Health Center in 2017 and no age relationship (p = 0.728) with anemia in pregnant women . Conclusion that age has no relationship with the incidence of anemia in pregnant women. Consumption of iron-containing foods is associated with the incidence of anemia in pregnant women. Suggestions for midwives who work at the KIA-KB Poli to continue to provide services according to operational standards during pregnancy examinations so that anemia in pregnant women can be treated and even prevented during pregnancy.